Pertumbuhan Bibit Pinang (Areca cactechu L.) dan Efisiensi Biaya Pemupukan pada Kombinasi Pupuk Kascing dan NPK - Nengsih, Yulistiati; Hayata, Hayata; Prasetyo, Try Putra; Adistya, Adilla; Andriyani, Lizyanti (Jurnal Media Pertanian, 2026)
The use of ultisol soil as a nursery medium is constrained by low soil fertility. This study aims to determine the growth of Areca nut seedlings (Areca catechu L.) in various compositions of vermicompost and NPK fertilizer in polybags to overcome the problem availability of nutrients in the soil. This study was conducted at the Experimental Station of the Faculty of Agriculture, Batanghari University on July 7 to November 2024. This study used a completely randomized design with one factor. The treatments were vermicompost and NPK fertilizer (k) with 6 levels as follows: k0=without vermicompost and NPK fertilizer, k1= 30 g vermicompost, k2= 10 g NPK fertilizer, k3= 22.5 g vermicompost + 2.5 g NPK fertilizer, k4= 15 g vermicompost + 5 g NPK fertilizer, k5= 7.5 g vermicompost + 7.5 g NPK fertilizer. The parameters observed were plant height, stem diameter, total leaf area, shoot dry weight, root dry weight, soil water content, root volume, soil chemical analysis. The combination treatment of vermicompost fertilizer with NPK fertilizer affected all parameters, namely plant height, stem diameter, total leaf area, shoot dry weight, root dry weight, and root volume. Based on data analysis, it can be said that the k5 treatment, namely a combination of 25% vermicompost fertilizer + 75% NPK fertilizer, will increase seedling height by 27.27%, seedling stem diameter by 50.10%, total leaf area by 65.40%, shoot dry weight by 64.55%, root dry weight by 130.57%, and root volume by 96.18% when compared to the control. The k1 treatment gave the highest value of planting media water content, increasing by 25.56% when compared to the control. The combination of vermicompost fertilizer with NPK fertilizer is highly recommended in areca nut cultivation. The cost of k5 fertilization increased by 7.25%, but there was an increase in seedling height of 12.5%; stem diameter 34.57%; total leaf area 49.23%; shoot dry weight 37%; root dry weight 35.58; soil water content 26.51%, and root volume 68%. The R/C ratio of areca nut seedlings was 1.87.